Fish oil protects against corn oil-induced cardiac insulin resistance and left ventricular dysfunction in rats via upregulation of PPAR-β/γ and inhibition of diacylglycerol/PCK axis activation. (May 2019) - Eid, Refaat A.; Al-Shraim, Mubarak; Eleawa, Samy M.; Zaki, Mohamed Samir Ahmed; El-kott, Attalla Farag; Eldeen, Muhammad Alaa; Alkhateeb, Mahmoud A.; Alassiri, Mohammed; Alderah, Hussain
Graphical abstract: Proposed mechanisms for the effect of corn oil and fish oil on cardiac insulin sensitivity. Highlights: HFD rich in corn oil induces peripheral cardiac IR and lipotoxicity in LVs of rats. Corn oil up-regulates cardiac PPARα and down-regulates PPARα/β in LV of rats. Fish oil/Corm oil ratio close to 1 prevents these adverse effects of corn oil. Fish oil up-regulates PPARα/β, down-regulates PPARα, and enhances LVs antioxidant potential. Abstract: This study investigated the effects corn oil (CO) and different ratios of corn oil plus fish oil (FO) on insulin signaling in rat's heart. Adult male rats were fed low (LFD) or isocaloric high-fat diets (HFDs) of CO alone or CO + FO (ratios of 9:1 or 4:1). Cultured cardiomyocytes were treated with linoleic acid (LA), DHA + EPA (1:1) or LA + (DHA + EPA) (1:1). CO induced peripheral and cardiac insulin resistance with mitochondria damage, lipotoxicity activation of PKCε. It also upregulated LV levels of PPARα and down regulated PPARβ/δ. FO antagonized corn oil effects at both ratio with more profound effects with the ratio of 4:1. The regulatory roles of CO and FO on PPARs was shown in cultured cardiomyocytes and independent of hyperinsulinemia or free fatty acids. In conclusion, reducing the ratio of n-6/n-3 PUFAs in our diet toward a value of one is cardioprotective.